Representasi QS. At-Taubah: 71 sebagai Landasan Menyikapi Perbuatan Munkar di Tengah Kebebasan Beragama - Heriansyah, Dafis (Jurnal Riset Agama, 2024)
This research is necessary to provide insight to the community in practicing amar ma’ruf nahi munkar as a foundation for addressing immoral actions in the context of religious freedom, based on QS. at-Taubah: 71. The aim of this study is to discuss amar ma’ruf nahi munkar as a basis for addressing immoral actions in the context of religious freedom, based on QS. at-Taubah: 71. The research method used is qualitative, with a literature study approach. Data sources were obtained through scholarly literature, including primary data (the Qur’an) and secondary data (books, journals, or similar materials related to the theme). The results and discussion conclude that addressing immoral actions can be done in three ways: preventing them with the hand, preventing them with the tongue, and lastly, preventing them with the heart. The weakest form of faith is rejecting immoral and disgraceful actions with the heart. This study recommends that the community address immoral actions in the context of religious freedom, based on QS. at-Taubah: 71. It also serves as a lesson for the community to reject disgraceful actions and provide guidance for those who practice what is good.